The use of sustainable river transport powered by solar energy: Viability and application in the city of Valdivia, Chile - Cavenaghi , Guilherme Alexandre Gallo; Arriagada, Carlos Andrés Hernández (Technical and Scientific Journal Green Cities, 2021)
Introduction - The article addresses an alternative to urban mobility through a case study of the vessel Solar Bier Express (Valdivia, Chile). Objective - To understand the technical and structural aspects of Solar, to evaluate its effectiveness as a new sustainable transport modality and the possibility of applying the model in other Latin American cities with territories on river edges. Methods - Consists of studying the structure and volume of the boat. To this end, four physical models and two virtual models were made. them reproduce the object of study on a reduced scale. Two other models were produced to understand volumetry, hydrodynamics and dimensioning of the vessel. Field research was also carried out with those who have already used Solar and a targeted interview with stakeholders. The data were obtained through a questionnaire on social networks and a visit to Valdivia, Chile. Results - Based on the models, it is understood how the vessel structure mechanism works that directly influences its navigability. Through volumetric studies, it was understood the interference of the hull shape in the hydrodynamics and stability of the Solar. As for field research and interview, most respondents understand Sustainable River Transport (T.F.S.) as an important contribution to local urban mobility, seeing great future potential. Conclusions - It is concluded that the current fleet is insufficient and there are problems related to local legislation, which does not recognize it as public transport, despite its potential. This modal can open doors to a sustainable future in Valdivia and, thus, serve as an example for other Latin American cities with river borders in their territories. KEYWORDS: Mobility. Sustainability. Boat.